2018
DOI: 10.1038/s41419-018-0673-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal glucocorticoid and mineralocorticoid receptors act cooperatively to regulate epidermal development and counteract skin inflammation

Abstract: Endogenous and synthetic glucocorticoids (GCs) regulate epidermal development and combat skin inflammatory diseases. GC actions can be mediated through the GC receptor (GR) and/or the mineralocorticoid receptor (MR), highly homologous ligand-activated transcription factors. While the role of GR as a potent anti-inflammatory mediator is well known, that of MR is not as clear, nor is whether these receptors cooperate or antagonize each other in the epidermis. To address this, we generated mice with epidermal-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 54 publications
5
79
0
Order By: Relevance
“…In MR EKO dermis, Nr3c2 levels increased by two-fold, and there was a trend toward increased GR activity (Figure 2a and b; two-fold, P ¼ 0.054). These changes were concomitant with the upregulation of Ddit4, Fkbp51, and Hsd11b1 in this compartment (2-fold, 7-fold, and 2.8-fold, respectively; Figure 2c), suggesting cooperative transcriptional effects of GR and MR (Bigas et al, 2018;Boix et al, 2016). The increased levels of Ddit4 and Fkbp51 are consistent with their reported role as skin atrophogenes, as the MR EKO dermis showed atrophy (Baida et al, 2018(Baida et al, , 2015 (Figure 1a and d).…”
Section: Middle-aged Mr Epidermal Knockout Skin Features Compartment-supporting
confidence: 83%
“…In MR EKO dermis, Nr3c2 levels increased by two-fold, and there was a trend toward increased GR activity (Figure 2a and b; two-fold, P ¼ 0.054). These changes were concomitant with the upregulation of Ddit4, Fkbp51, and Hsd11b1 in this compartment (2-fold, 7-fold, and 2.8-fold, respectively; Figure 2c), suggesting cooperative transcriptional effects of GR and MR (Bigas et al, 2018;Boix et al, 2016). The increased levels of Ddit4 and Fkbp51 are consistent with their reported role as skin atrophogenes, as the MR EKO dermis showed atrophy (Baida et al, 2018(Baida et al, , 2015 (Figure 1a and d).…”
Section: Middle-aged Mr Epidermal Knockout Skin Features Compartment-supporting
confidence: 83%
“…Boix et al(2016) demonstrated that epidermal deletion of MRs leads to increased keratinocyte proliferation and differentiation . Other studies proposed that epidermal MR cooperates with GC receptors, acting as an anti-inflammatory factor to counteract skin inflammation and regulate epidermal development in inflamed skin (Bigas et al, 2018;Sevilla and Pérez, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments demonstrate that the interaction of both receptors at the same target promoter, which occurs with different kinetics, results in specific and distinct transcriptional signatures and highlights the complexity of gene regulation by GR and MR [ 49 ]. In keratinocytes, GRs and MRs can heterodimerize in response to Dex and synergistically activate a GRE-luciferase reporter [ 50 ], however the relative binding of homo- and hetero-dimers to target genes in this cell type is unknown. An area of future interest is the identification of MBS in keratinocytes, as comparison of genomic bound regions in ChIP-seq experiments carried out in different cell types is limited by the well-known context and cell-type specific actions of these TFs.…”
Section: Transcriptional Regulation By Gr and Mrmentioning
confidence: 99%
“…HSD11B1 is expressed in human and mouse epidermis and dermis, and is upregulated in differentiating keratinocytes [ 60 , 61 ]. HSD11B2 is also present in human and mouse suprabasal epidermis as well as in sweat glands, an important target for aldosterone-MR regulation [ 10 , 50 , 62 , 63 , 64 ]. However, there is no evidence of local aldosterone synthesis in the epidermal or dermal cells of the skin [ 57 ].…”
Section: Systemic and Cutaneous Glucocorticoid/mineralocorticoid Pmentioning
confidence: 99%